The effect of investing in intellectual capital in reducing the total cost of comprehensive quality: an applied study in the General Company for Textile Industries - Hilla Textile Factory - Haider Ali Jarad Masoudi; Ali Qasim Hassan Al-Obeidi (Iraqi Journal for Administrative Sciences, 2024)
Study examined one important concept to most business organizations today is intellectual capital. This study was sought to shed light on this concept because it represents one of the most important factors in the success of the organizations, is that variable object helps the Department to achieve a number of other goals including reducing the total cost of quality overall has become a significant proportion compared to the total production costs. The study aims to achieve a set of objectives including determining the nature and essence of the relationship between two variables of the study, intellectual capital and the total cost of quality, demonstrate a compare of the impact of investment and the development of intellectual capital to the business organizations in managing these costs. The study adopted the hypothesis of a major effect that “there is significant correlation between intellectual capital and cost of total quality”. The study have a number of conclusions and recommendations that could contribute to improve the performance of economic units, especially the Iraqi, and help them to achieve their goals as required and correct